All-organic nano photosensitizer with high singlet oxygen generation activity as well as preparation method and application of all-organic nano photosensitizer

Through phosphorus doping and composite treatment, the all-organic nanophotographic agent P-C3N5/PDI was prepared, which solved the shortcomings of the existing graphite phase carbon nitride photosensitizer in terms of solar light absorption efficiency and singlet oxygen yield, and achieved high efficiency The singlet oxygen production and good water dispersion have broad application prospects.

CN119405803AActive Publication Date: 2025-02-11HUNAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411547491.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing graphite phase carbon nitride (g-C3N5) photosensitizers have insufficient solar light absorption efficiency and singlet oxygen yield, and most photosensitizers are insoluble in water and cannot be effectively enriched in tumors.

Method used

By thermal polymerization of 3-amino-1,2,4-triazole and tripolymerized phosphazene chloride, phosphorus-doped graphite phase carbon nitride (P-C3N5) was obtained, and then with 3,4,9,10 - Perylene tetraformyl diimine and nitric acid are combined and processed to form the all-organic nanophotographic agent P-C3N5/PDI, improving its water solubility and photodynamic properties.

Benefits of technology

This all-organic nanophotosensitizer can not only efficiently generate singlet oxygen, but also has good water dispersion and a wide visible light absorption range, significantly improves the photodynamic conversion efficiency and has potential application in cancer treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405803A_ABST
    Figure CN119405803A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photodynamic, in particular to an all-organic nano photosensitizer with high singlet oxygen generation activity as well as a preparation method and application of the all-organic nano photosensitizer. The preparation method comprises the following steps: mixing 3-amino-1, 2, 4-triazole and phosphonitrilic chloride trimer, and sequentially carrying out thermal polymerization reaction and copolymerization heat treatment to obtain P-C3N5; the method comprises the following steps: carrying out ultrasonic mixing on P-C3N5, a 3, 4, 9, 10-perylenetetracarboxylic diimide solution and water, standing, filtering, and washing and drying filter residues to obtain P-C3N5 / PDI; mixing the P-C3N5 / PDI with a nitric acid solution, carrying out heat treatment, and washing and drying the obtained heat-treated substance to obtain a dried substance; mixing the dried substance with sodium hydroxide and water, and then carrying out heating treatment to obtain a heated substance; and centrifuging the heated substance, and dialyzing the obtained clear liquid to be neutral to obtain the all-organic nano photosensitizer. The all-organic nano photosensitizer material has good water dispersibility and can efficiently generate singlet oxygen under near-infrared light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photodynamic technology, and in particular to an all-organic nano photosensitizer with high singlet oxygen generating activity and a preparation method and application thereof. Background Art

[0002] Graphitic carbon nitride (g-C3N5) is a metal-free photosensitizer. The skeleton characteristics of C3N5 describe and reveal its unique electronic structure and optical properties. Its unique skeleton characteristics make its band gap small, charge-hole separation efficiency high, and visible light absorption range wide. The high nitrogen atom content can also promote the transfer of electrons in C3N5. As a new type of semiconductor material, C3N5 has become a research hotspot due to its unique composition and structure as well as visible light dynamic activity. Compared with the existing more studied C3N4, C3N5 has a higher diffusion limiting current density and lower overpotential, which makes its photodynamic performance better. However, g-C3N5 can only absorb sunlight with a wavelength less than 500nm, and its solar energy conversion efficiency is still not ideal.

[0003] In order to further improve the photodynamic conversion efficiency of g-C3N5, various modification methods including structural regulation, doping with heteroelements, semiconductor or carbon material composites, etc. have been widely reported to increase reactive sites, enhance light absorption, and improve the separation / migration ability of carriers. Most photosensitizers are insoluble in water and cannot act on organisms, and have low enrichment efficiency in tumors and low singlet oxygen yield.

[0004] Therefore, there is an urgent need to develop a stable, low-cost and effective modification method to improve the photodynamic activity of g-C3N5, which can be soluble in water and efficiently produce singlet oxygen. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an all-organic nano photosensitizer with high singlet oxygen generating activity and a preparation method and application thereof. The all-organic nano photosensitizer prepared by the preparation method provided by the present invention is not only soluble in water, but also can efficiently generate singlet oxygen.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing an all-organic nano photosensitizer with high singlet oxygen generating activity, comprising the following steps:

[0008] 1) mixing 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performing thermal polymerization reaction and copolymerization heat treatment to obtain P-C3N5;

[0009] 2) mixing the P-C3N5 obtained in step 1) with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water by ultrasonication, letting the mixture stand and then filtering, washing and drying the filter residue to obtain P-C3N5 / PDI;

[0010] 3) mixing the P-C3N5 / PDI obtained in step 2) with a nitric acid solution, heat-treating the mixture, washing and drying the heat-treated mixture to obtain a dried mixture;

[0011] 4) mixing the dried product obtained in step 3) with sodium hydroxide and water and performing a heat treatment to obtain a heat-treated product;

[0012] 5) Centrifuging the heat-treated product obtained in step 4), dialyzing the resulting clear liquid to neutrality, and obtaining a fully organic nano photosensitizer.

[0013] Preferably, in step 1), the mass ratio of 3-amino-1,2,4-triazole to tripolyphosphazene chloride is 2:0.12.

[0014] Preferably, the conditions of the thermal polymerization reaction in step 1) include: temperature of 500° C., time of 4 h, and heating rate of 5° C. / min;

[0015] The conditions of the copolymerization heat treatment include: temperature of 550° C., time of 4 hours, and heating rate of 5° C. / min.

[0016] Preferably, in step 2), the volume ratio of the mass of P-C3N5 to the volume of the 3,4,9,10-perylenetetracarboxylic acid diimide solution and water is 0.6 g: 10 mL: 100 mL;

[0017] The solvent of the 3,4,9,10-perylenetetracarboxylic acid diimide solution is concentrated sulfuric acid, and the mass ratio of the volume of the concentrated sulfuric acid to the 3,4,9,10-perylenetetracarboxylic acid diimide is 10 mL:0.1 g;

[0018] The ultrasonic mixing time is 10 minutes and the power is 150W;

[0019] The standing time is 0.5h;

[0020] The pore size of the membrane used for the filtration is 0.45 μm;

[0021] The drying conditions include: temperature of 80° C. and time of 4 hours.

[0022] Preferably, in step 3), the volume ratio of the mass of P-C3N5 / PDI to the nitric acid solution is 1.5 g:25 mL;

[0023] The concentration of the nitric acid solution is 10 mol / L;

[0024] The heat treatment conditions include: temperature of 90° C. and time of 2 h.

[0025] Preferably, the mass ratio of the dried product to sodium hydroxide and water in step 4) is 0.18:1.8:60;

[0026] The conditions of the heating treatment include: temperature of 180° C. and time of 3 hours.

[0027] Preferably, the centrifugal conditions in step 5) include: a rotation speed of 8000 rpm and a time of 5 min;

[0028] The molecular weight cut-off of the dialysis bag used in the dialysis is 0.5KD.

[0029] The present invention also provides a fully organic nano photosensitizer prepared by the preparation method described in the above technical solution.

[0030] The present invention also provides the use of the all-organic nano photosensitizer described in the above technical solution in producing singlet oxygen.

[0031] Preferably, the method comprises the following steps:

[0032] The all-organic nano photosensitizer is mixed with a 1,3-diphenylisobenzofuran solution and reacted under near-infrared laser irradiation;

[0033] The volume ratio of the mass of the all-organic nano photosensitizer to the 1,3-diphenylisobenzofuran solution is 10 mg:2 mL;

[0034] The concentration of the 1,3-diphenylisobenzofuran solution is 1 mg / L;

[0035] The reaction time is more than 2 minutes.

[0036] The mechanism of the present invention for efficiently generating singlet oxygen is:

[0037] P element is doped into the aromatic heterocyclic structure of C3N5 to reduce its energy band. PDI is a rigid conjugated structure. Through acid hydrolysis and heating, PDI is recrystallized on C3N5 to form a heterojunction, establish an internal electric field, further reduce its energy band, inhibit the recombination of photogenerated carriers in the reaction process, improve the electron mobility in the reaction process, and expand the light absorption capacity and range of the material of the present invention. Under the excitation of light, the molecules of the material of the present invention can easily change from the ground state to the singlet excited state, and then change to the triplet excited state through intersystem crossing, and react with the surrounding O2 molecules to produce 1 O2.

[0038] Beneficial effects of the present invention:

[0039] The fully organic nano photosensitizer material with high singlet oxygen generation activity prepared by the present invention has a relatively wide visible light absorption range, greater visible light capture ability and good water dispersibility, and significantly improves the utilization rate of visible light. Experiments have verified that the photosensitizer material can efficiently generate singlet oxygen under near-infrared light and has a good photothermal effect, and has a relatively good development prospect in cancer treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0041] Figure 1 TEM image of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention;

[0042] Figure 2 This is a DLS graph of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano-photosensitizer material (P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention;

[0043] Figure 3 is the UV absorption spectra of different photosensitizers;

[0044] Figure 4 The fluorescence spectra of different photosensitizers;

[0045] Figure 5 This is a singlet oxygen performance test graph (λ=660nm) of a phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 1 of the present invention;

[0046] Figure 6 This is a singlet oxygen performance test graph (λ=808nm) of a phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 1 of the present invention;

[0047] Figure 7 The photothermal performance diagram (λ=660nm and 808nm) of a phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 1 of the present invention;

[0048] Figure 8This is a singlet oxygen performance test graph (λ=660nm) of a water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention;

[0049] Fig. 9 This is a singlet oxygen performance test graph (λ=808nm) of a water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention;

[0050] Fig.10 This is a photothermal performance diagram (λ=808nm) of a water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0051] The present invention provides a method for preparing an all-organic nano photosensitizer with high singlet oxygen generating activity, comprising the following steps:

[0052] 1) mixing 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performing thermal polymerization reaction and copolymerization heat treatment to obtain P-C3N5;

[0053] 2) mixing the P-C3N5 obtained in step 1) with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water by ultrasonication, letting the mixture stand and then filtering, washing and drying the filter residue to obtain P-C3N5 / PDI;

[0054] 3) mixing the P-C3N5 / PDI obtained in step 2) with a nitric acid solution, heat-treating the mixture, washing and drying the heat-treated mixture to obtain a dried mixture;

[0055] 4) mixing the dried product obtained in step 3) with sodium hydroxide and water and performing a heat treatment to obtain a heat-treated product;

[0056] 5) Centrifuging the heat-treated product obtained in step 4), dialyzing the resulting clear liquid to neutrality, and obtaining a fully organic nano photosensitizer.

[0057] 3-amino-1,2,4-triazole and tripolyphosphazene chloride are mixed and then subjected to thermal polymerization reaction and copolymerization heat treatment in sequence to obtain P-C3N5.

[0058] In the present invention, the mass ratio of the 3-amino-1,2,4-triazole to the tripolyphosphazene chloride is preferably 2:0.12. In the present invention, the conditions of the thermal polymerization reaction preferably include: a temperature of 500°C, a time of 4 hours, and a heating rate of 5°C / min. In the present invention, the conditions of the copolymerization heat treatment preferably include: a temperature of 550°C, a time of 4 hours, and a heating rate of 5°C / min.

[0059] The present invention mixes the obtained P-C3N5 with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water by ultrasonication, and then filters the mixture after standing. The filter residue is washed and dried to obtain P-C3N5 / PDI.

[0060] In the present invention, the mass ratio of the P-C3N5 to the volume of the 3,4,9,10-perylenetetracarboxylic acid diimide solution and the volume ratio of water is preferably 0.6g:10mL:100mL. In the present invention, the solvent of the 3,4,9,10-perylenetetracarboxylic acid diimide solution is preferably concentrated sulfuric acid, and the volume ratio of the concentrated sulfuric acid to the mass ratio of 3,4,9,10-perylenetetracarboxylic acid diimide is preferably 10mL:0.1g. In the present invention, the time of the ultrasonic mixing is preferably 10min, and the power is preferably 150W. In the present invention, the standing time is preferably 0.5h. In the present invention, the pore size of the membrane used for filtration is preferably 0.45μm. In the present invention, the drying conditions preferably include: a temperature of 80°C and a time of 4h.

[0061] The present invention mixes the obtained P-C3N5 / PDI with a nitric acid solution, performs heat treatment, washes and dries the obtained heat-treated product, and obtains a dried product.

[0062] In the present invention, the mass ratio of the P-C3N5 / PDI to the volume ratio of the nitric acid solution is 1.5 g:25 mL; the concentration of the nitric acid solution is preferably 10 mol / L. In the present invention, the heat treatment conditions preferably include: a temperature of 90° C. and a time of 2 h.

[0063] The present invention mixes the obtained dried product with sodium hydroxide and water and then performs heat treatment to obtain a heat-treated product. In the present invention, the mass ratio of the dried product to sodium hydroxide and water is 0.18:1.8:60. In the present invention, the conditions for the heat treatment preferably include: a temperature of 180°C and a time of 3 hours.

[0064] The present invention centrifuges the obtained heat-treated product, and dialyzes the obtained clear liquid to neutrality to obtain a fully organic nano photosensitizer. In the present invention, the centrifugal conditions include: a rotation speed of 8000 rpm and a time of 5 minutes. In the present invention, the molecular weight cutoff of the dialysis bag used for the dialysis is 0.5 KD.

[0065] The present invention also provides a fully organic nano photosensitizer prepared by the preparation method described in the above technical solution.

[0066] The present invention also provides the use of the all-organic nano photosensitizer described in the above technical solution in producing singlet oxygen.

[0067] In the present invention, the application preferably comprises the following steps:

[0068] The all-organic nano photosensitizer is mixed with a 1,3-diphenylisobenzofuran solution and reacted under near-infrared laser irradiation;

[0069] The volume ratio of the mass of the all-organic nano photosensitizer to the 1,3-diphenylisobenzofuran solution is 10 mg:2 mL;

[0070] The concentration of the 1,3-diphenylisobenzofuran solution is 1 mg / L;

[0071] The reaction time is more than 2 minutes.

[0072] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0073] Example 1

[0074] (1) Phosphorus-doped C3N5 nanosheets are called P-C3N5. Take 5 alumina crucibles respectively, weigh 2g of 3-AT (3-amino-1,2,4-triazole, content 96%) and 0.12g of HCCP (tripolychlorophosphazene, content 98%) in a mortar using an analytical balance, mix them thoroughly and grind them. After grinding, the obtained precursors are vacuum dried and placed in crucibles respectively after drying. The crucibles are placed in a muffle furnace and the heating program is set: thermal polymerization at 500℃ for 4h (heating rate of 5℃ / min). After the product is cooled naturally, it is ground again and placed in a muffle furnace for copolymerization heat treatment. The heating time is set to 4h, the heating rate is 5℃ / min, and the target temperature is 550℃. After the product is cooled naturally, the P-C3N5 sample is obtained.

[0075] (2) Weigh 0.1g of PDI (3,4,9,10-perylenetetracarboxylic acid diimide) and dissolve it in a beaker containing 10mL of concentrated sulfuric acid under ultrasonic treatment. Ultrasonicate the beaker for 10 minutes to fully dissolve it. Use an analytical balance to weigh 0.6g of P-C3N5 and add it to the beaker. Then add 100mL of deionized water to the beaker and continue ultrasonicating for 10 minutes. At this time, a solid insoluble precipitate will immediately appear in the beaker and stand for 0.5h. Then filter it through a 0.45μm membrane filter, collect the filtered solid, and wash it with deionized water several times. After washing, collect it and put it in a beaker, put the beaker into a drying oven for drying, the drying temperature is 80℃, and the drying time is 4h. After drying, P-C3N5 / PDI is obtained and marked as 6-P-C3N5PDI.

[0076] Comparative Example 1

[0077] The 0.6 g of P-C3N5 in step (2) of Example 1 was replaced with 0.2 g of P-C3N5, while other conditions remained unchanged, and it was marked as 2-P-C3N5PDI.

[0078] Comparative Example 2

[0079] The 0.6 g of P-C3N5 in step (2) of Example 1 was replaced with 0.4 g of P-C3N5, while other conditions remained unchanged, and it was marked as 4-P-C3N5PDI.

[0080] Comparative Example 3

[0081] The 0.6 g of P-C3N5 in step (2) of Example 1 was replaced with 0.8 g of P-C3N5, while other conditions remained unchanged, and it was labeled as 8-P-C3N5PDI.

[0082] Comparative Example 4

[0083] The 0.6 g of P-C3N5 in step (2) of Example 1 was replaced with 1.0 g of P-C3N5, while other conditions remained unchanged, and it was marked as 10-P-C3N5PDI.

[0084] Example 2

[0085] (1) Phosphorus-doped C3N5 nanosheets are called P-C3N5. Take 5 alumina crucibles respectively, weigh 2g of 3-AT (3-amino-1,2,4-triazole, content 96%) and 0.12g of HCCP (tripolychlorophosphazene, content 98%) in a mortar using an analytical balance, mix them thoroughly and grind them. After grinding, the obtained precursors are vacuum dried and placed in crucibles respectively after drying. The crucibles are placed in a muffle furnace and the heating program is set: thermal polymerization at 500℃ for 4h (heating rate of 5℃ / min). After the product is cooled naturally, it is ground again and placed in a muffle furnace for copolymerization heat treatment. The heating time is set to 4h, the heating rate is 5℃ / min, and the target temperature is 550℃. After the product is cooled naturally, the P-C3N5 sample is obtained.

[0086] (2) Weigh 0.1g of PDI (3,4,9,10-perylenetetracarboxylic acid diimide) and dissolve it in a beaker containing 10mL of concentrated sulfuric acid under ultrasonic treatment. Ultrasonicate the beaker for 10 minutes to fully dissolve it. Use an analytical balance to weigh 0.6g of P-C3N5 and add it to the beaker. Then add 100mL of deionized water to the beaker and continue ultrasonicating for 10 minutes. At this time, a solid insoluble precipitate will immediately appear in the beaker and stand for 0.5h. Then filter it through a 0.45μm membrane filter, collect the filtered solid, and wash it with deionized water several times. After washing, collect it and put it in a beaker, and put the beaker into a drying oven for drying. The drying temperature is 80℃ and the drying time is 4h. After drying, block P-C3N5 / PDI is obtained.

[0087] (3) The P-C3N5 / PDI powder was ground in ethanol with a grinding mortar for 10 minutes to make the powder finer, and then dried in air at 70°C to obtain fine P-C3N5 / PDI powder. 1.5 g of P-C3N5 / PDI powder was dispersed in a brown sealed bottle containing (10 mol / L, 25 mL) nitric acid solution and heated at 90°C for 2 hours. The acid-treated powder was washed with deionized water several times and then dried at 90°C. 0.18 g of the dried powder was mixed with 1.8 g NaOH and 60 mL water and stirred. The solution was then transferred to a 150 mL Teflon-lined stainless steel autoclave, and then the sealed autoclave was heated to 180°C in an electric oven and maintained for 3 hours. After cooling naturally to room temperature, the product was centrifuged at 8000 rpm for 5 minutes to remove large-sized particles, and the supernatant obtained by centrifugation was dialyzed in a dialysis bag (molecular weight cutoff of 0.5 KD) for two days and exchanged with deionized water until its pH was close to neutral, thereby obtaining the final water-soluble P-C3N5 / PDI nano-photosensitizer material.

[0088] Figure 1This is a TEM image of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano-photosensitizer material (P-C3N5 / PDI) with high singlet oxygen generation activity obtained in Example 2 of the present invention. Figure 1 It can be seen that the synthesized water-soluble P-C3N5 / PDI nano-photosensitizer material has a size between 50nm and 110nm and has an irregular flake structure.

[0089] Figure 2 This is a DLS graph of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano-photosensitizer material (P-C3N5 / PDI) with high singlet oxygen generation activity obtained in Example 2 of the present invention. Figure 2 It can be seen that the particle size of the water-soluble P-C3N5 / PDI nano-photosensitizer material synthesized in the experiment is mainly distributed between 87nm and 150nm, among which the particle size of 100nm to 125nm is the majority.

[0090] Figure 3 The UV absorption spectra of different photosensitizers are shown in Figure 2. Figure 3 It can be seen that the water-soluble P-C3N5 nanophotosensitizer has a visible absorption edge near 250nm, and the water-soluble PDI has a wide absorption in the 200nm-400nm band. When P-C3N5 and PDI are hybridized, a significant absorption peak appears at 250nm-370nm, with two absorbance edges, indicating that the water-soluble P-C3N5 / PDI nanophotosensitizer has a wider range of visible light harvesting capabilities. The maximum absorption peak shifts to the near-infrared band, and the maximum absorption peak intensity is significantly improved. This phenomenon shows that the interfacial interaction between PDI and P-C3N5 connects the heterostructures together through chemical bonds.

[0091] Figure 4 Fluorescence spectra of different photosensitizers. Figure 4 The fluorescence spectra of P-C3N5 / PDI nano photosensitizer materials under different wavelengths of light excitation are shown in the figure. Under the excitation of different wavelengths of light, it can be seen from the figure that the peak of the fluorescence spectrum is approximately fixed between 440nm and 500nm, and the spectrum type has nothing to do with the wavelength of the excitation light. However, the fluorescence intensity of the water-soluble P-C3N5 / PDI photosensitizer is closely related to the wavelength of the excitation light, and the peak value changes with the change of the excitation light wavelength. It can be seen from the figure that the P-C3N5 / PDI nano photosensitizer has the strongest fluorescence emission under 320nm excitation, and the peak position is at 452nm.

[0092] Combination Figure 1-4It can be seen that the water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer material (P-C3N5 / PDI) with high singlet oxygen production activity prepared in the present invention has the advantages of small size, strong light absorption ability, good water dispersibility, and good photodynamic performance.

[0093] Example 3

[0094] A study on the photodynamic activity of a phosphorus-doped graphite phase carbon nitride-perylene diimide all-organic heterojunction photosensitizer with high singlet oxygen generation activity includes the following steps:

[0095] Take the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-P-C3N5 / PDI) prepared in Implementation Example 1 of the present invention, the photosensitizer (2-P-C3N5 / PDI) prepared in Comparative Example 1, the photosensitizer (4-P-C3N5 / PDI) prepared in Comparative Example 2, and the photosensitizer (8-P-C3N5 / PDI) prepared in Comparative Example 3, take 10 mg of each, add them to 2 mL of 1,3-diphenylisobenzofuran (DPBF) solution with a concentration of 1 mg / L, mix well, take samples, and measure their absorbance at 410 nm and time zero in an ultraviolet spectrophotometer. Subsequently, the mixture was stirred and reacted for 2.5 min under laser irradiation (λ=660 nm and 808 nm, power of 0.2 W), and a sample was taken, transferred to a cuvette, and its absorbance at 2.5 min was measured in a UV spectrophotometer. Similarly, the absorbance was measured after stirring and reacting under laser for 5 min, 7.5 min, and 10 min, respectively.

[0096] Control group 1: acetonitrile was used to replace 6-P-C3N5 / PDI, and other conditions were the same.

[0097] Control group 2: C3N5 was used to replace 6-P-C3N5 / PDI, and other conditions were the same.

[0098] Control group three: P-C3N5 was used to replace 6-P-C3N5 / PDI, and other conditions were the same.

[0099] A study on the photothermal effect of a phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic photosensitizer with high singlet oxygen generation activity includes the following steps:

[0100] Take 10 mg of each of the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic photosensitizers (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Implementation Example 1 of the present invention, irradiate with near-infrared laser (λ=660nm and 808nm, power of 0.2W) for 1 min, and record the temperature change every 10 seconds using an infrared thermal imager.

[0101] Figure 5This is a singlet oxygen performance test graph (λ=660nm) of a phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic photosensitizer (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 1 of the present invention. Figure 5 As shown in (a), when the 660nm laser is used as the irradiation light source and the full spectrum of ultraviolet absorption is measured, the photosensitizer has the maximum absorbance at 410nm, and the maximum absorption range is between 350nm and 450nm. Figure 5 (b) is a graph showing the intensity changes of the ultraviolet-visible absorption light of DPBF at 410nm under the irradiation of a 660nm laser with different photosensitizer materials. It is obvious from the C / C0 in the figure that after 10 minutes of reaction, the six photosensitizer materials prepared in the experiment all have the ability to produce singlet oxygen to a certain extent, and the absorbance has decreased to a certain extent. After the start of illumination, the six photosensitizers all caused a certain degree of degradation of DPBF, showing an accelerating trend. The degree of decrease in absorbance in the 4-P-C3N5 / PDI group, the 6-P-C3N5 / PDI group, and the 8-P-C3N5 / PDI group was almost 90%, which was much greater than the degree of decrease in absorbance in the other four control groups, producing 1 O2 is the most abundant. Figure 5 As shown in (c), the degradation of DPBF follows the first-order reaction kinetic equation, and the fitting curve is a straight line, which shows that it is a first-order reaction. After fitting the curve, the degradation rate constant k value of DPBF when using different photosensitizers under 660nm laser is summarized in Figure 5 In (d), it can be seen that under 660nm laser irradiation, 6-P-C3N5 / PDI photosensitizer produces 1 The rate constant k of O2 is 0.21681min -1 , which is significantly higher than other photosensitizers. It can be concluded that the 6-P-C3N5 / PDI photosensitizer synthesized in this experiment produces 1 O2 is more active.

[0102] Table 1 660nm Figure 5 Zhonga full spectrum detection data

[0103]

[0104]

[0105]

[0106] Table 2 660nm Figure 5 Medium (bd) data

[0107]

[0108]

[0109] Figure 6 This is a singlet oxygen performance test graph (λ=808nm) of a phosphorus-doped graphite-phase carbon nitride-perylene diimide all-organic heterojunction photosensitizer (6-P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 1 of the present invention. Figure 6 As shown in (a), when the 808nm laser is used as the irradiation light source and the full spectrum of ultraviolet absorption is measured, the photosensitizer has the maximum absorbance at 410nm, and the maximum absorption range is between 350nm and 450nm. Figure 6 (b) is a graph showing the intensity changes of the ultraviolet-visible absorption light of DPBF at 410nm under 808nm laser irradiation for the six photosensitizer materials. It is obvious from the C / C0 in the figure that after the reaction starts, the six nanophotosensitizers prepared in the experiment all have the ability to produce singlet oxygen to a certain extent. After 10 minutes of reaction, the absorbance of the 6-P-C3N5 / PDI group decreases the fastest, producing 1 O2 is the most abundant. Figure 6 As shown in (c), the degradation of DPBF follows the first-order reaction kinetic equation, and the fitting curve is a straight line, which shows that it is a first-order reaction. After fitting the curve, the degradation rate constant k value of DPBF when using different photosensitizers under 808nm laser is summarized in Figure 6 In (d), it can be seen that under 808nm laser irradiation, 6-P-C3N5 / PDI photosensitizer produces 1 The rate constant k of O2 is 0.07205min -1 , which is significantly higher than other photosensitizers. It can be concluded that the 6-P-C3N5 / PDI nano photosensitizer synthesized by the present invention produces 1 O2 is more active.

[0110] Table 3808nm Figure 6 Medium a data

[0111]

[0112]

[0113]

[0114] Table 4808nm Figure 6 Medium (bd) data

[0115]

[0116] Figure 7 This is a photothermal effect diagram of a phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic photosensitizer (6-P-C3N5 / PDI) with high singlet oxygen generation activity obtained in Example 1 of the present invention. Figure 7It can be seen that when the near-infrared laser (λ = 660nm and 808nm, power of 0.2W) is used as the irradiation light source, the photosensitizer (6-P-C3N5 / PDI) has a significant heating effect within 1 minute. Under 660nm laser irradiation, the temperature of the photosensitizer (6-P-C3N5 / PDI) rises to 92.1°C within 1 minute. Under 808nm laser irradiation, the temperature of the photosensitizer (6-P-C3N5 / PDI) rises to 78.9°C within 1 minute. It can be concluded that the photosensitizer (6-P-C3N5 / PDI) has good photothermal capacity under near-infrared laser irradiation.

[0117] Example 4

[0118] A study on the photodynamic activity of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano-photosensitizer material with high singlet oxygen generation activity comprises the following steps:

[0119] Take 10 mg of the water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer (P-C3N5 / PDI) prepared in Example 2 of the present invention, add them to 2 mL of 1,3-diphenylisobenzofuran (DPBF) solution with a concentration of 1 mg / L, mix them evenly, take samples, and measure their absorbance at 410 nm and zero time in an ultraviolet spectrophotometer. Then stir and react for 2 min under laser (λ=660 nm and 808 nm, power of 0.2 W), take samples, transfer them to a cuvette, and measure their absorbance at 2 min in an ultraviolet spectrophotometer, and so on, respectively measure their absorbance after stirring and reacting for 4 min, 6 min, 8 min, and 10 min under laser.

[0120] Control group 1: Acetonitrile was used to replace water-soluble P-C3N5 / PDI, and other conditions were the same.

[0121] Control group 2: water-soluble C3N4 was used to replace water-soluble P-C3N5 / PDI, and other conditions were the same.

[0122] Control group three: water-soluble C3N5 was used to replace water-soluble P-C3N5 / PDI, and other conditions were the same.

[0123] Control group 4: water-soluble P-C3N5 was used to replace water-soluble P-C3N5 / PDI, and other conditions were the same.

[0124] Control group 5: water-soluble PDI was used to replace water-soluble P-C3N5 / PDI, and other conditions were the same.

[0125] A photothermal effect study of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano-photosensitizer material with high singlet oxygen generation activity, comprising the following steps:

[0126] Take 10 mg of the water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer (P-C3N5 / PDI) prepared in Example 2 of the present invention, irradiate it with a near-infrared laser (λ=808 nm, power of 2 W) for 1 min, and record the temperature change every 10 s using an infrared thermal imager.

[0127] Figure 8 This is a singlet oxygen performance test diagram (λ=660nm) of a water-soluble phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic nano photosensitizer (P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention. Figure 8 As shown in (a), when the 660nm laser is used as the irradiation light source and the full spectrum of ultraviolet absorption is measured, the photosensitizer has the maximum absorbance at 410nm, and the maximum absorption range is between 400nm and 460nm. Figure 8 (b) is a graph showing the intensity changes of the ultraviolet-visible absorption light of DPBF at 410nm under the irradiation of a 660nm laser with different photosensitizer materials. It can be clearly seen from the C / C0 in the figure that after 10 minutes of reaction, the five photosensitizer materials prepared in the experiment all have the ability to produce singlet oxygen to a certain extent, and the absorbance has decreased to a certain extent. After the start of illumination, the five photosensitizers all caused a certain degree of degradation of DPBF, showing an accelerating trend, but after 2 minutes, the rates of the five groups slowed down, but the overall trend was still downward. After 10 minutes of illumination and stirring, the absorbance reduction of the water-soluble P-C3N5 / PDI group reached 47%, which was much greater than the absorbance reduction of the other four control groups. It was the highest among the five photosensitizers prepared in the experiment. 1 O2 has the best effect. Figure 8 As shown in (c), the degradation of DPBF follows the first-order reaction kinetic equation, and the fitting curve is a straight line, which shows that it is a first-order reaction. After fitting the curve, the degradation rate constant k value of DPBF when using different photosensitizers under 660nm laser is summarized in Figure 8 (d). It can be seen that under 660nm laser irradiation, the water-soluble P-C3N5 / PDI photosensitizer produces 1 The rate constant k of O2 is 0.05683min -1 , which is significantly higher than other photosensitizers. It can be concluded that the water-soluble P-C3N5 / PDI nano-photosensitizer synthesized in this experiment produces 1 O2 is more active.

[0128] Table 5660nm Figure 8 Zhonga full spectrum detection data

[0129]

[0130]

[0131]

[0132] Table 6660nm Figure 8 Medium (bd) data

[0133] X-axis DPBF <![CDATA[C3N4]]> <![CDATA[C3N5]]> <![CDATA[P-C3N5]]> PDI P-CN / PDI 0 1 1 1 1 1 1 2 1 0.9375 0.92577 0.93305 0.92224 0.81044 4 0.96051 0.88636 0.87255 0.85251 0.86999 0.73376 6 0.95159 0.83665 0.81933 0.78661 0.8068 0.67838 8 0.9465 0.78977 0.77451 0.72071 0.75699 0.60703 10 0.93121 0.75 0.72689 0.67469 0.69988 0.54526

[0134] Fig. 9 This is a singlet oxygen performance test graph (λ=808nm) of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic nano-photosensitizer (P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention. Fig. 9 As shown in (a), when the 808nm laser is used as the irradiation light source and the full spectrum of ultraviolet absorption is measured, the photosensitizer has the maximum absorbance at 425nm, and the maximum absorption range is between 410nm and 450nm. Fig. 9 (b) is a graph showing the intensity changes of the ultraviolet-visible absorption light of DPBF at 410nm under 808nm laser irradiation for the five photosensitizer materials. It can be clearly seen from the C / C0 in the figure that after 10 minutes of reaction, the five nanophotosensitizers prepared in the experiment all have a certain degree of ability to produce singlet oxygen. After the start of illumination, in the first two minutes, the absorbance of the water-soluble P-C3N5 / PDI nanophotosensitizer group decreased the fastest. After irradiation with 808nm laser and stirring for 10 minutes, the absorbance reduction of the water-soluble P-C3N5 / PDI group reached 28%. Compared with the absorbance reduction of the other four groups, the absorbance reduction of the water-soluble P-C3N5 / PDI group is better. Fig. 9 As shown in (c), the degradation of DPBF follows the first-order reaction kinetic equation, and the fitting curve is a straight line, which shows that it is a first-order reaction. After fitting the curve, the degradation rate constant k value of DPBF when using different photosensitizers under 808nm laser is summarized in Fig. 9 In (d), it can be seen that under 808nm laser irradiation, the water-soluble P-C3N5 / PDI photosensitizer produces 1 The rate constant k of O2 is 0.00275min -1 , slightly lower than that of water-soluble P-C3N5 photosensitizer 1 The rate constant of O2. It can be seen that the water-soluble P-C3N5 / PDI photosensitizer produces 1 O2 is more active.

[0135] Table 7808nm Fig. 9Zhonga full spectrum detection data

[0136]

[0137]

[0138]

[0139] Table 8808nm Fig. 9 Medium (bd) data

[0140] X-axis DPBF <![CDATA[C3N4]]> <![CDATA[C3N5]]> <![CDATA[P-C3N5]]> PDI P-CN / PDI 0 1 1 1 1 1 1 2 0.99899 0.9869 0.94237 0.90772 0.95965 0.8838 4 0.97588 0.95161 0.90822 0.83661 0.92456 0.83333 6 0.96382 0.9244 0.88154 0.77761 0.89211 0.79108 8 0.95075 0.89315 0.83885 0.7292 0.80702 0.74648 10 0.93568 0.85988 0.80256 0.68381 0.75088 0.71714

[0141] Fig.10 This is a photothermal effect diagram of a water-soluble phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic photosensitizer (P-C3N5 / PDI) with high singlet oxygen generation activity prepared in Example 2 of the present invention. Fig.10 It can be seen that when the near-infrared laser (λ=808nm, power of 0.2W) is used as the irradiation light source, the photosensitizer (P-C3N5 / PDI) has an obvious heating effect within 1 minute. Under the irradiation of 808nm laser, the temperature of the photosensitizer (P-C3N5 / PDI) rises to 64.9°C within 1 minute. It can be concluded that the photosensitizer (P-C3N5 / PDI) has good photothermal capacity under the irradiation of near-infrared laser.

[0142] In summary, the all-organic nano photosensitizer material with high singlet oxygen generation activity of the present invention has a relatively wide visible light absorption range, greater visible light capture ability and good water dispersibility, and significantly improves the utilization rate of visible light. Experiments have verified that the photosensitizer material can efficiently generate singlet oxygen under near-infrared light and has a good photothermal effect, and has a relatively good development prospect in cancer treatment.

[0143] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an all-organic nano photosensitizer with high singlet oxygen generation activity, characterized in that: The following steps are involved: 1) mixing 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performing thermal polymerization reaction and copolymerization heat treatment to obtain P-C3N5; 2) mixing the P-C3N5 obtained in step 1) with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water by ultrasonication, letting the mixture stand and then filtering, washing and drying the filter residue to obtain P-C3N5 / PDI; 3) mixing the P-C3N5 / PDI obtained in step 2) with a nitric acid solution, heat-treating the mixture, washing and drying the heat-treated mixture to obtain a dried mixture; 4) mixing the dried product obtained in step 3) with sodium hydroxide and water and performing a heat treatment to obtain a heat-treated product; 5) Centrifuging the heat-treated product obtained in step 4), dialyzing the resulting clear liquid to neutrality, and obtaining a fully organic nano photosensitizer.

2. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of 3-amino-1,2,4-triazole to tripolyphosphazene chloride is 2:0.

12.

3. The preparation method according to claim 1, characterized in that: The conditions of the thermal polymerization reaction in step 1) include: temperature of 500° C., time of 4 hours, and heating rate of 5° C. / min; The conditions of the copolymerization heat treatment include: temperature of 550° C., time of 4 hours, and heating rate of 5° C. / min.

4. The preparation method according to claim 1, characterized in that: In the step 2), the volume ratio of the mass of P-C3N5 to the volume of the 3,4,9,10-perylenetetracarboxylic acid diimide solution and water is 0.6 g: 10 mL: 100 mL; The solvent of the 3,4,9,10-perylenetetracarboxylic acid diimide solution is concentrated sulfuric acid, and the mass ratio of the volume of the concentrated sulfuric acid to the 3,4,9,10-perylenetetracarboxylic acid diimide is 10 mL:0.1 g; The ultrasonic mixing time is 10 minutes and the power is 150W; The standing time is 0.5h; The pore size of the membrane used for the filtration is 0.45 μm; The drying conditions include: temperature of 80° C. and time of 4 hours.

5. The preparation method according to claim 1, characterized in that: In step 3), the volume ratio of the mass of P-C3N5 / PDI to the nitric acid solution is 1.5 g:25 mL; The concentration of the nitric acid solution is 10 mol / L; The heat treatment conditions include: temperature of 90° C. and time of 2 h.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the dried product to sodium hydroxide and water in step 4) is 0.18:1.8:60; The conditions of the heating treatment include: temperature of 180° C. and time of 3 hours.

7. The preparation method according to claim 1, characterized in that: The centrifugal conditions in step 5) include: a rotation speed of 8000 rpm and a time of 5 min; The molecular weight cut-off of the dialysis bag used in the dialysis is 0.5KD.

8. The all-organic nano photosensitizer prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the all-organic nano photosensitizer according to claim 8 in producing singlet oxygen.

10. The use according to claim 9, characterized in that: The following steps are involved: The all-organic nano photosensitizer is mixed with a 1,3-diphenylisobenzofuran solution and reacted under near-infrared laser irradiation; The volume ratio of the mass of the all-organic nano photosensitizer to the 1,3-diphenylisobenzofuran solution is 10 mg:2 mL; The concentration of the 1,3-diphenylisobenzofuran solution is 1 mg / L; The reaction time is more than 2 minutes.

Citation Information

Patent Citations

  • Carboxyl-containing perylene bisimide / oxygen-doped carbon nitride nanosheet heterojunction photocatalyst as well as preparation method and application thereof

    CN111389458A

  • G-C3N4 / PTCDI-Br composite material as well as preparation method and application thereof

    CN112574237A

  • Preparation method and application of two-photon mediated CN-PDI nanoparticles

    CN114306600A

  • Preparation method of all-organic composite photocatalytic material for photocatalytic production of hydrogen peroxide

    CN114669315A

  • PDI / g-C3N4 Z-type heterojunction catalyst as well as preparation method and application thereof

    CN117696115A